Curriculum reform and classroom practice: teaching geography in the Zimbabwean Curriculum Framework 2015 – 2022 - Madondo, Manasa Munashe (University of the Free State, 2020)
Zimbabwe is currently in the throes of implementing whole-curriculum reforms encased in the Zimbabwe Curriculum Framework for Primary and Secondary Education 2015 to 2022 (ZCF 2015-2022). One of the major aims of this competence-based curriculum drive is the adoption of learner-centred pedagogy. An understanding of how Zimbabwean teachers make sense and enact the learner-centred instructional policy was a lacuna which this study sought to address. The research focuses on how four purposively sampled form 3 and 4 geography teachers from archetypical secondary schools, made sense of and enacted the ZCF 2015-2022 mandated learner-centred pedagogy. The study adopted a multiple-case study design using techniques of documentary study, observations, interviews, and self-reporting instruments namely; reflective self- journaling and a learner-centred practices gauge to generate qualitative data that yielded the following three main findings, in line with the research’s sub-questions. Firstly, though well-articulated policy signals abound in flagship policy documents, teachers lacked adequate understanding of these signals due to ineffective pre-implementation induction. The resultant policy-practice gap reflects discordant understandings between change-agents and local actors. Secondly, although all four teachers professed support for learner-centred pedagogy, each held individual perceptions on teaching. The commonly espoused support for learner-centred pedagogy was traceable to initial teacher training pro-learner-centred courses. Such espousal also reflected respondent biases of; ‘social desirability’ and ‘social acquiescence’ associated with data generated through self-check instruments where respondents want to look good and agree with what they know is the ideal. The four teachers also held individual sense-making understandings of teaching. A third finding was that there was scanty evidence on teachers’ voiced support for learner-centred methods in observed lessons. Observed teacher-centred question-and-answer sessions failed to attain effective levels of learner-centredness. However, some observed lessons approximated the ZCF 2015-2022 learner-centred policy mandate. This was partly due to factors as; participation in staff development courses, membership to a professional learning community and ability to create Rich Environments for Active Learning. The study recommends, an Integrated Eclectic Cognitive Sense-Making Framework, for an inclusive process of curriculum policy implementation with potential for meaningful local actor sense-making in enacting mandated reforms.
Thesis (Ph.D. (Education Studies))--University of the Free State, 2020
Keywords: Sense-making; Competence-based curriculum; Learner-centred pedagogy; Change-agents; Local actors; Policy enactment; Professional learning community; Rich environments for active learning